Analysis of the regulation on handeling sharpening waste generated during the treatment of outpatients - Novoa Munevar, Claudia Yanet
The objective of this article is to present the results of a documentary review on the management, classification and regulation of sharp residues generated by outpatients. This seeks to characterize the problem of the management of such wastes, in their different stages: a) segregation at the source; (b) internal management at the hospital level; and c) delivery of waste for final disposal. Legal elements related to safety, occupational health and environmental conservation are also taken as a reference. For this purpose, the sanitary route, own for the management of containers within health institutions, is established as a reference, and how the proposal of a portable container of such sharp elements could be articulated within the Route. Methodology: In order to analyze information related to comprehensive waste management, the use of articles published in the period from 2009 to 2019, for which the use of consulted indexed databases such as BVS, Dialnet, Scielo, Redalyc, PubMed and BioMed Central, and Science direct. Colombia is chose as a geographical reference. Equally National legislation on the subject was also consulted on the pages of the Ministry of National Protection, the Ministry of Health and INVIMA. As regards the exclusion criteria, the following were raised: legislation prior to 2008; articles in English and grey literature. It takes place in four parts: a first part where the treatment of sharp elements is contextualized in the United States and the United Kingdom; the second time the legal background on the disposal of sharp waste is discussed; in the third moment, the identification of the legal framework is carried out as the basis for the development of the prototype of the portable container; and a fourth section identifies the forward impulses given from climate change that relate to the disposal of sharp waste. As a conclusion it is proposed that it is necessary to use containers that comply with current regulations, eco-friendly, that provide protection against their use, handling, collection and corresponding storage for patients who are in contact with this type of Waste.